Penerapan Pembelajaran Seni Berbasis Steam: Studi Kasus Pembelajaran Musik Di TK Kemala Bhayangkari 34 Kendal - MS Viktor Purhanudin (Journal on Education, 2025)
This study aims to analyze the concept and practice of STEAM-based art education (Science, Technology, Engineering, Arts, and Mathematics) at TK Kemala Bhayangkari 34 Kendal. The main focus of this research is to explore how the concept of art education, specifically music, is implemented within the STEAM framework at this school, as well as to examine how the practice is carried out by the teachers. The research employs a descriptive qualitative method with a case study approach, utilizing observation, interviews, and document analysis. The findings reveal that the teachers at TK Kemala Bhayangkari 34 Kendal have a strong understanding of the STEAM concept and successfully integrate its elements into music education. The lessons include sound wave experiments, creating musical instruments from recycled materials, and the use of digital music applications to introduce technology. Despite challenges related to limited resources and varying student abilities, the STEAM-based learning practice at this school has successfully created an engaging learning experience that enhances creativity, collaboration, and problem-solving skills. This study also shows that STEAM-based learning is highly relevant for early childhood education as it helps children connect various disciplines in a fun and practical way. Based on these findings, it is recommended that the STEAM approach be further implemented in early childhood education to support the holistic development of students.